2018
DOI: 10.5130/ajceb.v18i2.5882
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health and Safety Risk Levels of Building Construction Trades in Nigeria

Abstract: This study assessed the occupational health and safety risk-level of common building construction trades in Nigeria. It also identified the sources, frequency and magnitude of risks inherent in the activities of various building construction trades. Being site-based survey research, it made use of a structured questionnaire administered to the selected building construction workers of different trades in Anambra State, Nigeria. The collected data were subjected to quantitative risk analysis using mean value me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
0
20
1
1
Order By: Relevance
“…Several considerations for enhancing CS during IPh have been reported by different researchers. In previous studies [9,[34][35][36][37], 20 factors were identified: (1) scaffolding, (2) ladder access to heights, (3) mobile scaffolds, (4) workplace access, (5) housekeeping, (6) roof work, (7) personal protective equipment, (8) mobile-elevated work platforms, (9) site safety information documents, (10) plan of action, (11) competency of workers and ongoing training, (12) monitoring system, (13) hazard reporting, (14) accident reporting, (15) incidents/near misses, (16) discipline, (17) Health and Safety Authority(HSA) inspections, (18) communication in the workplace, (19) responsibility for safety in the workplace and (20) cooperation. International laws, regulations and specifications have discussed safety requirements in CPs as labour laws [38], such as Occupational Safety and Health Agreement No.…”
Section: Introductionmentioning
confidence: 87%
“…Several considerations for enhancing CS during IPh have been reported by different researchers. In previous studies [9,[34][35][36][37], 20 factors were identified: (1) scaffolding, (2) ladder access to heights, (3) mobile scaffolds, (4) workplace access, (5) housekeeping, (6) roof work, (7) personal protective equipment, (8) mobile-elevated work platforms, (9) site safety information documents, (10) plan of action, (11) competency of workers and ongoing training, (12) monitoring system, (13) hazard reporting, (14) accident reporting, (15) incidents/near misses, (16) discipline, (17) Health and Safety Authority(HSA) inspections, (18) communication in the workplace, (19) responsibility for safety in the workplace and (20) cooperation. International laws, regulations and specifications have discussed safety requirements in CPs as labour laws [38], such as Occupational Safety and Health Agreement No.…”
Section: Introductionmentioning
confidence: 87%
“…The health and safety performance of construction organisations in the construction industry of Nigeria is poor. This is evident in the submission of Okoye (2018). It was posited that in Nigeria, construction tradespeople are still being exposed to injuries, disease, and fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of extant studies on health and safety on construction projects that sampled construction professionals, consultants, clients, or contractors (Abas et al, 2020;Agyekum et al, 2018;Belayutham & Ibrahim, 2019;Chen et al, 2020;Mohammed et al, 2015;Williams et al, 2019). While only a limited number of them sampled construction tradespeople (artisans, craftsmen, operatives), who are the set of workers carrying out the actual building production work (Kukoyi & Smallwood, 2017;Okoye, 2018;Tanko et al, 2020). Kukoyi & Smallwood (2017) carried out a qualitative study of Health and Safety (H&S) Construction Practices in Lagos.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed model is important for construction practice. Based on a large set of data on accidents included in the CKD, it is possible to study the impact of the following on the accidentality phenomenon: Technologies used in the construction industry, the types of carried out construction works, and the methods used to organize work and equipment.publications [4][5][6]. In order to increase the level of occupational safety in the construction industry, a detailed analysis of the accidentality phenomenon should be conducted, the circumstances and main causes for the occurrence of this phenomenon should be identified, and intensive and continuous preventive actions should also be carried out.The main purpose of the research presented in the article is to examine the characteristic features of the accidentality phenomenon as a process that creates a sequence of accidents that occur at discrete moments of time on various construction sites in terms of their location, construction, and technical equipment.…”
mentioning
confidence: 99%
“…publications [4][5][6]. In order to increase the level of occupational safety in the construction industry, a detailed analysis of the accidentality phenomenon should be conducted, the circumstances and main causes for the occurrence of this phenomenon should be identified, and intensive and continuous preventive actions should also be carried out.…”
mentioning
confidence: 99%